Effect of Vitamin D Supplementation During Pregnancy on Birth Weight: An Experimental Study in Rats - Sari, Widia; Khudri, Ghaniyyatul; Zeffira, Laura; Handayani, Kurnia Maidarmi (Biomedical Journal of Indonesia, 2025)
Introduction. Vitamin D deficiency, commonly observed during pregnancy, can affect fetal growth, which can be evaluated by birth weight. Vitamin D supplementation during pregnancy is anticipated to beneficially affect birth weight, a crucial factor for neonatal health and long-term health outcomes. Methods. This research was conducted using an in vivo experimental design on Rattus norvegicus rats as animal models. This study involved 24 rat pups from four groups of pregnant rats, each provided with standard feed and varying doses of vitamin D supplementation: Group A received 62 IU/kgBW, Group B received 415 IU/kgBW, Group C received 663 IU/kgBW, and Group D received no vitamin D supplementation. Vitamin D supplementation was provided through oral gavage from the first day of gestation until parturition. At the time of delivery, six pups from each group were randomly chosen to measure their birth weights. Results. The finding from this research indicated that vitamin D supplementation during pregnancy positively influenced birth weight (p<0.001). The birth weights of pups in Group C were significantly higher compared to those in group D (p<0.001) and Group A (p<0.001). Pups in Group B also had significantly higher birth weights compared to Group D (p=0.002) and Group A (p=0.006). Conclusion. Based on these findings it can be concluded that vitamin D supplementation at doses 415 IU/kgBW and 663 IU/kgBW can increase birth weight.